Effects of dietary astaxanthin on the growth performance and carcass characteristics of finishing pigs - Bergstrom, J.R.; Houser, Terry A.; Gunderson, J.A.; Gipe, A.N.; Jacela, J.; Benz, J.M.; Sulabo, R.C.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 48 barrows (initially 215 lb) were used to evaluate the effects of increasing dietary astaxanthin (0, 5, 10, and 20 ppm) on late-finishing pig performance and carcass characteristics. Pigs were blocked by weight and randomly allotted to 1 of 4 dietary treatments in a 26-d experiment. Pigs were fed simple corn-soybean meal-based diets. Treatments consisted of a control diet and the control diet with 5, 10, or 20 ppm added astaxanthin. For overall growth performance (d 0 to 26), ADG and F/G of pigs fed astaxanthin was not different from that of the control pigs. However, ADFI tended (linear; P < 0.10) to decrease with increasing astaxanthin. For the comparison of carcass characteristics, pigs fed increasing astaxanthin had decreased average (P < 0.03) and 10th rib (P < 0.06) backfat depth compared with control pigs. Pigs fed 5 or 10 ppm astaxanthin tended to have the lowest (quadratic; P < 0.10) 10th rib fat depth. Pigs fed increasing astaxanthin tended to have increased (quadratic; P < 0.10) standardized fat-free lean and percentage of fat-free lean, and pigs fed 5 or 10 ppm were the leanest. The loin muscle of pigs fed astaxanthin tended to have lower L* and b* (P < 0.06 and P < 0.08, respectively), indicating a darker color. The improved carcass characteristics of pigs fed astaxanthin resulted in a numeric increase in the net profit per pig for those fed 5 and 10 ppm astaxanthin. In conclusion, growth performance of pigs fed 5, 10, or 20 ppm astaxanthin was not different from that of pigs fed the control diet. However, the improved carcass characteristics could be economically beneficial to pork producers. Additionally, the improvements observed in loin color could result in improved consumer acceptance of fresh pork. These results warrant further research.
Keywords: Astaxanthin; Carcass characteristics; Pork color; Swine